+0  
 
0
93
2
avatar+52 

Solve the equation.

 

(2x+6)^1/3 - (6x-1)^1/3 =0

 

Select the correct choice below and, if necessary, fill in the answer box to complete your choice.

 

A. the solution set is____.

B. There is no solution

 

 

Thank you in advance

yojaymarojas  May 14, 2017
edited by yojaymarojas  May 14, 2017
Sort: 

2+0 Answers

 #1
avatar+89775 
+1

Solve the equation.

 

(3x+4)^1/3 - (5x-1)^1/3 =0

 

\((3x+4)^{1/3} - (5x-1)^{1/3} =0\\ (3x+4)^{1/3} = (5x-1)^{1/3} \\ 3x+4=5x-1\\ 5=2x\\ x=2.5\)

Melody  May 14, 2017
 #2
avatar+75324 
+2

Just a slight error on Melody's part ....

 

(2x+6)^1/3 - (6x-1)^1/3 =0

 

Following the same procedure as Melody, we arrive at

 

2x + 6  =  6x - 1 

 

4x    =   7

 

x  =  7/4  =  1.75

 

 

cool cool cool

CPhill  May 14, 2017

16 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details